2015
DOI: 10.3109/23744235.2015.1022873
|View full text |Cite
|
Sign up to set email alerts
|

Association between respiratory viruses and exacerbation of COPD: a case-control study

Abstract: The current study investigated the probable roles of the respiratory viruses, and dual infections during acute exacerbations of COPD. Since climate-dependent respiratory viral incidence patterns in Iran are often dissimilar, preparing a comprehensive global model of respiratory infections with seasonal details in different geographical zones might decrease the morbidity and mortality rate in exacerbations of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
2
28
2
Order By: Relevance
“…Other viruses such as HADV, RSVA and HCoV were detected in low rates, at 1.5%, 1.5% and 1.21%, respectively. This was inconsistent with some study results, for example Hosseini et al found that HADV was highly detected virus at a rate of 9.4%. Similarly, Dimopoulos et al found RSV at a rate of 28.5% and Greenberg et al found HCoV at a rate of 4.9%.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Other viruses such as HADV, RSVA and HCoV were detected in low rates, at 1.5%, 1.5% and 1.21%, respectively. This was inconsistent with some study results, for example Hosseini et al found that HADV was highly detected virus at a rate of 9.4%. Similarly, Dimopoulos et al found RSV at a rate of 28.5% and Greenberg et al found HCoV at a rate of 4.9%.…”
Section: Discussioncontrasting
confidence: 91%
“…Flu (FluA and FluB) was highly detected virus. Our results were consistent with the study results by Koul et al, Tan et al and Biancardi et al, but inconsistent with the study results by Hosseini et al, Dimopoulos et al, Kherad et al and Greenberg et al The characteristics of Flu frequently occurred in the temperate zones, especially in East Asia, which might be another reason for the prevalence of H7N9 virus infection in China . HRV prevalence was followed by Flu, which was inconsistent with the study results by Wilkinson et al, Djamin et al and Varkey et al in Euro‐American region.…”
Section: Discussioncontrasting
confidence: 63%
“…Besides the respiratory symptoms, the patients with viral exacerbation presented more frequent non-respiratory symptoms (fever, muscle pain) and a longer symptoms remission time (15 days vs 9 days). 30 The seasonal pattern of COPD exacerbations described in the TORCH study 31 was also demonstrated in other studies. 25,26 Most viral infections usually occur in winter, followed by summer, autumn and spring.…”
Section: Introductionsupporting
confidence: 72%
“…In addition, this study evidenced dual viral infection present in 22.2% of AECOPD patients. Besides the respiratory symptoms, the patients with viral exacerbation presented more frequent non‐respiratory symptoms (fever, muscle pain) and a longer symptoms remission time (15 days vs 9 days) …”
Section: Microorganismsmentioning
confidence: 99%
“…Of lesser prevalence were coronaviruses (4%), parainfluenza (3%), human metapneumovirus (3%) and adenovirus (2%). 28 Coinfection with two or more viruses has also been reported, 36 with one study noting that in their cohort, only the patients with viral co-infections were severe enough to be admitted to the hospital for their exacerbations. 34 While simultaneous bacterial and viral pathogens have been detected during acute exacerbations, it remains unclear whether these co-infections carry any greater risk for poor outcomes in comparison to single infections.…”
Section: Acute Infection In Copd: Viral and Bacterial Superinfection mentioning
confidence: 99%